Balochistan Women in Politics: An Examination of Political Participation and its Effects on Women Empowerment in Balochistan, Pakistan - Kakar, Muhammad Makki; Rahim, Muhammad; Ali, Shoukat (Pakistan Journal of Humanities and Social Sciences, 2023)
This research paper investigates women's political participation and its impact on women's political empowerment in Balochistan, Pakistan. With women constituting half of the population, their role in various domains, including political development, is crucial. The study focuses on women political workers from eight political parties, namely ANP, BNP-Mengal, NP, HDP, PkMAP, PML-N, PPPP, and PTI, operating in Balochistan. A sample of 400 respondents was selected from these parties to gather insights into women's political participation and empowerment in the region. The findings reveal a positive trend of increasing women's political participation and empowerment in Balochistan. Moreover, the study emphasizes encouraging women to contribute and play significant roles in society actively. This research sheds light on women's political involvement in Balochistan and highlights the potential for further progress in empowering women through political engagement.